La intervención psicopedagógica en la atención educativa a niños con trastornos del espectro autista de la Unidad Educativa Nuevo Oeste - Auria García, Kelly Dariana (2023)
Autism is one of the disorders that is occurring with the greatest recurrence in recent times. Teachers from their role are not trained to face this challenge, so psychopedagogical intervention is imminent in the educational context that makes it possible to approach it from the classroom, applying appropriate strategies and adjusted to the needs of each student with autism. The purpose of this work was to analyze the influence of psychopedagogical intervention in educational care for children with Autism Spectrum Disorders from the "Nuevo Oeste" Educational Unit using a type of descriptive research, with a qualitative approach. The information collected was obtained through research instruments such as observation sheets and interviews applied in the Educational Institution. The results achieved were analyzed and showed the little follow-up of the teacher by the psychopedagogue in the domain of pedagogical strategies to implement students with autism. On the other hand, since the institution does not have a psychopedagogue, it was evident that there is a great importance of the actions of this specialist in the contexts of educational development. Therefore, it was recommended to systematically plan training for all managers of the education of students with autism.